Resin infiltration for esthetic improvement of mild fluorosis in a patient with autism spectrum disorder: A 36-month follow-up (Research, Society and Development, 2022)
Report a case using a minimally invasive technique (ICON®) to treat mild dental fluorosis in an adolescent with an autism spectrum disorder. Male patient, 15 years old, diagnosed with autism spectrum disorder, with the chief complaint of white spots on anterior teeth resulting in low self-esteem. Upon clinical examination, opaque white areas were observed in the enamel of all teeth, compatible with the diagnosis of mild dental fluorosis. As the patient has a mild degree of autism spectrum disorder and exhibits collaborative behavior, the treatment of choice was the resin infiltration in the maxillary incisors, canines, and first premolars. The step-by-step application was carried out according to the manufacturer’s recommendations under the rubber dam. An immediate improvement in the appearance of fluorosis was significant, and the aesthetic result was satisfactory, with color stability after 36 months of follow-up. Resin infiltration was excellent for treating mild dental fluorosis, improving aesthetics, and easy of application. Additionally, the infiltrant obtained color stability 36 months after treatment and met the expectations of the patient and his family. Aesthetics should be considered when they impact their lives, facilitating care in these cases is essential to complete treatment.